Critério de seleção de bombas de circulação usadas para aquariofilia com base na ecoeficiência - Arantes, Fábio Soares (2020)
This study aims to develop a selection criterion for circulation pumps used for aquarism based on eco-efficiency. For the development of this selection criterion, the segment was analyzed, where the cost of imported circulation pumps was taken into account versus the cost of national circulation pumps, and introducing the analysis of the energy consumption of these circulation pumps, which was not emphasized until then by specialists in this segment. The research methodology was carried out through a field research in 30 aquarium stores, with the objective of evaluating the form of selection for analysis in decision making regarding the acquisition of national or imported circulation pumps, aiming at eco-efficiency. The results showed that for some flow rates, imported circulation pumps do not have national competitors, making them the only options on the market. With regard to other flows, where national pumps are manufactured, the field research showed that experts in the sector do not consider energy consumption as a form of selection. Pareto's analysis showed that the most important requirements reported by the experts interviewed, were that the pumps must have good price and good quality. It was also found that most experts do not adopt any selection criteria that consider ecoefficiency. This can make a low-cost pump for the consumer to have a high total cost, by spending more energy for its performance, burdening the consumer and using more natural resources for its operation, compromising eco-efficiency. With respect to circulation pumps used for aquarism, this dissertation has as scientific contribution the proposition of: (1) a classification according to its flow rates, and (2) a complementary form for a selection criterion, based on eco-efficiency, contributing to the formation of a sustainable culture, where everyone contributes what they can, in the best possible way, to the sustainability of the Planet.